Diverse Roles of Mitochondria in Immune Responses: Novel Insights Into Immuno-Metabolism - Angajala, Anusha; Lim, Sangbin; Phillips, Joshua B.; Kim, Jin-Hwan; Yates, Clayton; You, Zongbing; Tan, Ming (Frontiers in Immunology, 2018)
Lack of immune system cells or impairment in differentiation of immune cells is the basis for many chronic diseases. Metabolic changes could be the root cause for this immune cell impairment. These changes could be a result of altered transcription, cytokine production from surrounding cells, and changes in metabolic pathways. Immunity and mitochondria are interlinked with each other. An important feature of mitochondria is it can regulate activation, differentiation, and survival of immune cells. Additionally, it can also release signals such as mtDNA and mtROS to regulate transcription of immune cells. From current literature, we found that mitochondria can regulate immunity in different ways. Firstly, alterations in metabolic pathways (TCA cycle, OXPHOS, and FAO) and mitochondria induced transcriptional changes can lead to entirely different outcomes in immune cells. For example, M1 macrophages exhibit a broken TCA cycle and have a pro-inflammatory role. In contrast, M2 macrophages undergo β-oxidation to produce anti-inflammatory responses. Additionally, amino acid metabolism, especially arginine, glutamine, serine, glycine, and tryptophan, is critical for T cell differentiation and macrophage polarization. Secondly, mitochondria can activate the inflammatory response. For instance, MAVS signaling and NLRP3 can be activated by mitochondria. Thirdly, mitochondrial mass and mobility can be influenced by fission and fusion. Fission and fusion can influence immune functions. Lastly, mitochondria are placed near the endoplasmic reticulum (ER) in immune cells. Therefore, mitochondria and ER junction signaling can also influence immune cell metabolism. Mitochondrial machinery such as metabolic pathways, amino acid metabolism, antioxidant systems, mitochondrial dynamics, mtDNA, mitophagy, and mtROS are crucial for immune functions. Here, we have demonstrated how mitochondria coordinate to alter immune responses and how changes in mitochondrial machinery contribute to alterations in immune responses. A better understanding of the molecular components of mitochondria is necessary. This can help in the development of safe and effective immune therapy or prevention of chronic diseases. In this review, we have presented an updated prospective of the mitochondrial machinery that drives various immune responses.